Thirty Days of Montmorency Tart Cherry Supplementation Has No Effect on Gut Microbiome Composition, Inflammation, or Glycemic Control in Healthy Adults - Hillman, Angela R.; Chrismas, Bryna C. R. (Frontiers in Nutrition, 2021)
Tart cherries possess properties that may reduce inflammation and improve glycemic control, however human data on supplementation and the gut microbiota is equivocal. Furthermore, processing (i.e., juice concentrate, dried, frozen) may affect the properties of tart cherries, and therefore alter their efficacious health benefits. Therefore, the purpose of this study was to investigate the effect of 30 days of supplementation with Montmorency tart cherry (MTC) in concentrate or freeze-dried form on the gut microbiome and markers of inflammation and glycemic control. Healthy participants with no known disease (n=58, age: 28 ± 10 y, Height: 169.76 ± 8.55 cm, body mass: 72.2 ± 12.9 kg) were randomly allocated to four groups and consumed either concentrate or freeze-dried capsules or their corresponding placebos for 30 days. Venous blood samples were drawn at baseline, day 7, day 14 and day 30 and analyzed for inflammatory markers TNF-alpha, uric acid, C-reactive protein, and erythrocyte sedimentation rate and glycemic control markers glycated albumin, glucose and insulin. A fecal sample was provided at baseline, day 14 and day 30 for microbiome analysis. TNF-alpha was significantly lower at 30 days vs. 14 days (p=0.01), however there was no other significant change in the inflammatory markers. Insulin was not changed over time (p=0.16) or between groups (p=0.24), nor was glycated albumin different over time (p = 0.08) or between groups (p = 0.56), however glucose levels increased (p < 0.001) from baseline (4.79 ± 1.00 mmol‧L-1) to 14 days (5.21 ± 1.02 mmol‧L-1) and 30 days (5.61 ± 1.22 mmol‧L-1) but this was no different between groups (p=0.33). There was no significant change in composition of bacterial phyla, families, or subfamilies for the duration of this study nor was there a change in species richness. These data suggest that 30 days of MTC supplementation does not modulate the gut microbiome, inflammation, or improve glycemic control in a healthy, diverse group of adults. This trial was registered at: https://clinicaltrials.gov/ct2/show/NCT04467372